ECONOMY AS A PHENOMENON OF CULTURE: THEORETICAL AND METHODOLOGICAL ANALYSIS - S. N. Ivaskovsky (Vestnik MGIMO-Universiteta)
The article redefines economy as a phenomenon of culture, a product of a historically and socially grounded set of values shared by members of a given society. The research shows that culture is not always identical to social utility, because there are multiple examples when archaic, traditionalist, irrational cultural norms hinder social and economic progress and trap nations into poverty and underdevelopment. One of the reasons for the lack of scholarly attention to cultural dimension of economy is the triumph of positivism in economics. Mathematics has become the dominant language of economic analysis. It leads to the transformation of the economics into a sort of «social physics», accompanied by the loss of its original humanitarian nature shared in the works of all the great economists of the past. The author emphasizes the importance of the interdisciplinary approach to the economic research and the incorporation of the achievements of the other social disciplines – history, philosophy, sociology and cultural studies - into the subject matter of economic theory. Substantiating the main thesis of the article, the author shows that there is a profound ontological bond between economy and culture, which primarily consists in the fact that these spheres of human relations are aimed at the solution of the same problem – the competitive selection of the best ways for survival of people, of satisfying the relevant living needs. In order to overcome the difficulties related to the inclusion of culture in the set of analytical tools used in the economic theory, the author suggests using a category of «cultural capital», which reestablishes the earlier and more familiar for the economists meaning of capital.